Novel Application of Hydrotropic Solubilization in the Spectrophotometric Analysis of Paracetamol Tablet - Maheshwari, R.K.; Dewangan, A.; Soni, P.K.; Kansagra, P.K.; Jain, S.K. (Asian Journal of Chemistry, 2010)
Concentrated aqueous solutions of various hydrotropic agents like sodium salicylate, sodium benzoate, sodium citrate, sodium acetate, urea and nicotinamide have been observed to enhance aqueous solubilities of a large number of poorly water-soluble drugs. In the present investigation, paracetamol has been selected as a poorly water-soluble drug. There was more than 7-fold enhancement in aqueous solubility of paracetramol by 10.0 M urea solution (as compared to its aqueous solubility). This hydrotropic agent was employed to solubilize the drug from the fine powder of tablet formulations. The selected λmax for spectrophotometric estimation was 245 nm. The hydrotropic agent and additives used in the manufacture of tablets did not interfere in the analysis. Proposed method is new, rapid, simple, accurate and reproducible. Statistical data proved the accuracy, reproducibility and the precision of the proposed method.